Experimental and numerical analysis of fracture in 41Cr4 steel - issues of the stationary cracks - Graba, Marcin (Zielona Góra: Uniwersytet Zielonogórski)
This paper analyzes the process of fracture in 41Cr4 steel on the basis of experimental and numerical data obtained for non-propagating cracks. The author?s previous and latest experimental results were used to determine the apparent crack initiation moment and fracture toughness for the material under plane strain conditions. Numerical simulations were carried out to assess changes in the J-integral, the crack tip opening displacement, the size of the plastic region and the distribution of stresses around the crack tip. A complex numerical analysis based on the true stress-strain curve was performed to determine the behavior of 41Cr4 steel under increasing external loads.
Keywords: 40H steel; FEM; J-integral; CTOD; crack initiation moment; stress distribution; parameters of the geometric constraints; plastic region